Nationwide Population-Based Study About Patterns of Prescription Opioid Use and Misuse Among Young Adults in Spain - Carrasco-Garrido, Pilar; Gallardo-Pino, Carmen; Jiménez-Trujillo, Isabel; Hernández-Barrera, Valentín; García-Gómez-Heras, Soledad; Lima Florencio, Lidiane; Palacios-Ceña, Domingo (International Journal of Public Health, 2022)
Objective: Prescription opioid misuse has become one of the most common ways drugs are consumed among young adults. The objective of our study was to describe the prevalence and factors associated with prescription opioid use and misuse among young adults living in Spain. Methods: A nationwide, cross-sectional epidemiological study on the use and misuse of prescription opioids in Spanish Youngers. We used individualized secondary data provided by the Household Survey on Alcohol and Drugs in Spain 2017–2018. Results: Prevalence of prescription opioid use among young adults was 4.89%. Misuse among this population reached prevalence values of 13.4%, with higher values observed among women . The variables associated with a greater probability of prescription opioid use and misuse were misuse of tranquilizers, sedatives, and sleeping pills, along with using cannabis and other illicit psychoactive drugs (aOR=2.99; 95% CI: 1.10–8.15). Conclusions: Prescription opioid use and misuse in Youngers has important implications for the Spanish public health system, because, even though not currently comparable to the situation in other countries, this drug use could be on the verge of creating similar problems.